All-Trans Retinoic Acid Promotes an M1- to M2-Phenotype Shift and Inhibits Macrophage-Mediated Immunity to Leishmania major - Vellozo, Natália S.; Pereira-Marques, Sâmara T.; Cabral-Piccin, Mariela P.; Filardy, Alessandra A.; Ribeiro-Gomes, Flávia L.; Rigoni, Thaís S.; DosReis, George A.; Lopes, Marcela F. (Frontiers in Immunology, 2017)
As key cells, able to host and kill Leishmania parasites, inflammatory monocytes/macrophages are potential vaccine and therapeutic targets to improve immune responses in Leishmaniasis. Macrophage phenotypes range from M1, which express NO-mediated microbial killing, to M2 macrophages that might help infection. Resistance to Leishmaniasis depends on Leishmania species, mouse strain, and both innate and adaptive immunity. C57BL/6 (B6) mice are resistant and control infection, whereas Leishmania parasites thrive in BALB/c mice, which are susceptible to develop cutaneous lesions in the course of infection with Leishmania major, but not upon infection with Leishmania braziliensis. Here, we investigated whether a deficit in early maturation of inflammatory monocytes into macrophages in BALB/c mice underlies increased susceptibility to L. major versus L. braziliensis parasites. We show that, after infection with L. braziliensis, monocytes are recruited to peritoneum, differentiate into macrophages, and develop an M1 phenotype able to produce proinflammatory cytokines in both B6 and BALB/c mice. Nonetheless, more mature macrophages from B6 mice expressed inducible NO synthase (iNOS) and higher NO production in response to L. braziliensis parasites, whereas BALB/c mice developed macrophages expressing an incomplete M1 phenotype. By contrast, monocytes recruited upon L. major infection gave rise to immature macrophages that failed to induce an M1 response in BALB/c mice. Overall, these results are consistent with the idea that resistance to Leishmania infection correlates with improved maturation of macrophage in a mouse-strain and Leishmania-species dependent manner. All-trans retinoic acid (ATRA) has been proposed as a therapy to differentiate immature myeloid cells into macrophages and help immunity to tumors. To prompt monocyte to macrophage maturation upon L. major infection, we treated B6 and BALB/c mice with ATRA. Unexpectedly, treatment with ATRA reduced proinflammatory cytokines, iNOS expression, and parasite killing by macrophages. Moreover, ATRA promoted an M1 to M2 transition in bone marrow-derived macrophages from both strains. Therefore, ATRA uncouples macrophage maturation and development of M1 phenotype and downmodulates macrophage-mediated immunity to L. major parasites. Cautions should be taken for the therapeutic use of ATRA, by considering direct effects on innate immunity to intracellular pathogens.